Is a polymorphism in 10q25 associated with non-syndromic cleft lip with or without cleft palate? A meta-analysis based on limited evidence. Issue 1 (January 2015) - Li, Chun; Li, Zhaoyang; Zeng, Xuewen; Guo, Zhilong
Abstract Non-syndromic cleft lip with or without cleft palate (NSCL/P) is one of the most common defects in the human facial structure. A polymorphism, rs7078160 in 10q25, has been reported to be involved in susceptibility to the condition but results remain conflicting. To address this we did a meta-analysis of 7 eligible studies. Two authors independently collected information from the papers, and fixed effects or random effects models were used to calculate the combined estimates of risk. The pooled results showed that rs7078160 on 10q25, the minor allele A, had a higher risk of NSCLP than the major allele G (OR: 1.32, 95% CI: 1.18 to 1.47). Overall, the results showed that the 10q25 rs7078160 polymorphism was associated with a risk of NSCL/P.